Chromosomal microarray analysis in fetuses with an isolated congenital heart defect: A retrospective, nationwide, multicenter study in France. (29th April 2019) - Hureaux, Marguerite; Guterman, Sarah; Hervé, Bérénice; Till, Marianne; Jaillard, Sylvie; Redon, Sylvie; Valduga, Myléne; Coutton, Charles; Missirian, Chantal; Prieur, Fabienne; Simon‐Bouy, Brigitte; Beneteau, Claire; et al.
Abstract: Objectives: Congenital heart defects (CHDs) may be isolated or associated with other malformations. The use of chromosome microarray (CMA) can increase the genetic diagnostic yield for CHDs by between 4% and 10%. The objective of this study was to evaluate the value of CMA after the prenatal diagnosis of an isolated CHD. Methods: In a retrospective, nationwide study performed in France, we collected data on all cases of isolated CHD that had been explored using CMAs in 2015. Results: A total of 239 fetuses were included and 33 copy number variations (CNVs) were reported; 19 were considered to be pathogenic, six were variants of unknown significance, and eight were benign variants. The anomaly detection rate was 10.4% overall but ranged from 0% to 16.7% as a function of the isolated CHD in question. The known CNVs were 22q11.21 deletions (n = 10), 22q11.21 duplications (n = 2), 8p23 deletions (n = 2), an Alagille syndrome (n = 1), and a Kleefstra syndrome (n = 1). Conclusion: The additional diagnostic yield was clinically significant (3.1%), even when anomalies in the 22q11.21 region were not taken into account. Hence, patients with a suspected isolated CHD and a normal karyotype must be screened for chromosome anomalies other than 22q11.21 duplications and deletions. Abstract : What's already known about this topic? The use of a chromosome microarray can increase the genetic diagnostic yield for isolated congenital heart defects by between 4% and 10%. What does this study add? Broader use of chromosome microarrays is essential for the etiologic diagnosis of isolated congenital heart defects and will help to identify new candidate genes involved in cardiogenesis.